Desarrollo mediante ddRADseq y aplicación de nuevos marcadores SSR en pecán para identificación de cultivares - Rivas, Juan Gabriel; Aguirre, Natalia Cristina; Garcia, Martin Nahuel; Acuña, Cintia Vanesa; Villalba, Pamela Victoria; Grassi, Ana Laura; Frusso, Enrique Alberto; Ceballos, Dario Sebastian; Martinez, Maria Carolina; Marcucci Poltri, Susana Noemi (INIA, 2026)
Poster